Anesthetic management of Amplatzer atrial septal defect closure device embolization to right ventricular outflow tract - Das, S (Saudi J Anaesth, 2016)
Percutaneous device closure of atrial septal defect (ASD) is an alternative treatment to surgery with advantages of avoidance of surgery, short procedure time, early discharge from hospital, and lower rates of complications. However, percutaneous device closure is associated with infrequent life-threatening complications such as device embolization. We report a case device embolization of the ASD occlude device into right ventricular outflow tract resulting progressive hypoxia. The role of anesthesiologist as a team leader in managing such emergency is discussed.